The Influence of Dance Learning on The Development of Self-Confidence in Children Aged 5-6 Years at RA Khairu Ummah, Purwodadi Village, Sunggal District, Deli Serdang Regency, Academic Year 2022/2023 - Annisa, Rizky; Damanik, Suri Handayani (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
The study aimed to explain that there was a significant effect of learning dance on the self-confidence of children aged 5-6 years at RA Khairu Ummah Sunggal for the 2022/2023 Academic Year. The type of research used in this research is quantitative research using experimental methods. The results of the hypothesis test, "Independent Sample Test" in the Equal variances section are assumed to know the Sig value. (2-tailed) is 0.000 < 0.05 meaning that Ho is rejected and Ha is accepted. Also, the consulted tcount obtained is greater than ttable, namely 2.00 < 6,761 > 2.65. Thus it can be concluded that there is a significant difference between the average results of increasing the confidence of children aged 5-6 years at RA Kairu Ummah in the creative dance learning group (experiments) and traditional dance learning groups (control).